ANALISIS PRODUKSI TEBU DAN GULA DI PT. PERKEBUNAN NUSANTARA VII (PERSERO) - Derry Candia Apriawan; Irham Irham; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2015)
The study was conducted in Bungamayang District PT. Perkebunan Nusantara VII (Persero), Lampung Province. The objective of this study are: (1) to see the trend of production, productivity and input use of sugarcane and sugar production, (2) to know factors affecting production of sugarcane, (3) to identify factors affecting production of sugar, and (4) to estimate the profit of sugar and molasses. The method used was descriptive quantitative analysis. Sampling location was determined by purposively. The data used are secondary data during 30 years (1984-2013). Trend analysis, multiple linear regression (Cobb-Douglas function), and profit analysis we used in this study. The results of trend analysis show that the production of sugar, sugar productivity, and rendemen has a positive trend, while the number of labour has a negative trend. The result of regression analysis shows that increase in harvested area could increase the production of sugarcane. The result of regression analysis also shows that increase in harvested area, rendemen, and rainfalls could increase the production of sugar, post amalgamation Bungamayang District and PT. Perkebunan Nusantara VII (Persero) could give better sugar production, while the increase in the number of labour would decrease the production of sugar because the number of labour has reached the maximum level. From the results of the study show that the highest profit of sugar and molasses in Bungamayang District PT. Perkebunan Nusantara VII (Persero) is the Ratoon Cane I cropping pattern, followed by Ratoon Cane II, Ratoon Cane III, and the lowest profit obtained in Plant Cane.